PENGARUH HARGA, WORD OF MOUTH DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA UD. MAKMUR JAYA DI DESA BUGEMAN KENDIT KABUPATEN SITUBONDO - Fadilah, Sohibul; Soeliha, Siti; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2024)
This study aimed to determine the role of customer satisfaction in mediating price, word of mouth, and service quality on consumer loyalty at UD Makmur Jaya. The population in this study was consumers who bought products at UD Makmur Jaya. The sampling technique used in this study was probability sampling using random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model—Partial Least Square (PLS-SEM). The results showed that price has a significant effect on Consumer Satisfaction. Word Of Mouth has a significant effect on Customer Satisfaction. Service quality has a significant effect on customer satisfaction. Price has a significant effect on Consumer Loyalty. Word Of Mouth has a significant effect on Customer Satisfaction. Service quality has a significant effect on consumer loyalty. Consumer Satisfaction has a significant effect on Consumer Loyalty. Word Of Mouth has a significant effect on Consumer Loyalty through Consumer Satisfaction. Service Quality has a significant effect on Consumer Loyalty through Consumer Satisfaction.